Aesthetic Value And Symbolic Meaning In The Performance Of Segoro Topeng Kaliwungu: A Study Of Cultural Semiotics - Emi yuliastutik; Trisakti Trisakti; Retnayu Prasetyanti Sekti (Jurnal Impresi Indonesia, 2025)
The Segoro Topeng Kaliwungu performance is a form of traditional art that is rich in aesthetic values and symbolic meanings. This article aims to analyze the aesthetic values contained in the performance and interpret the implied symbolic meanings through a cultural semiotic perspective. Using a qualitative approach and descriptive analysis methods, this study examines the visual, auditory, and kinesthetic elements in the performance to reveal the cultural messages it wants to convey. The results of the analysis show that every aspect of the Segoro Topeng Kaliwungu performance, from costumes, music, dance movements, to story narratives, contains symbols that reflect the social values, beliefs, and history of the Kaliwungu community. A deep understanding of these aesthetic values and symbolic meanings is important for the preservation and development of traditional performing arts in the modern era.